Relation - Alpsancar, Suzana (Lexikon der Raumphilosophie)

Das Leuphana College: Ein in Europa einzigartiges Hochschulmodell – Studienstruktur. - Beck, Karin; Gunkel, Marjaana; Seifert, Andreas; Schütz, Julia; Scharlau, Ingrid (DGHD-Tagung „Professionalisierung der Hochschuldidaktik”)

Making Use of Multi-Modal Synchrony: A Model of Acoustic Packaging to Tie Words to Actions - Wrede, Britta; Schillingmann, Lars; Rohlfing, Katharina (Theoretical and Computational Models of Word Learning: Trends in Psychology and Artificial Intelligence)
If they are to learn and interact with humans, robots need to understand actions and make use of language in social interactions. Hirsh-Pasek and Golinkoff (1996) have emphasized the use of language to learn actions when introducing the idea of acoustic packaging in human development. This idea suggests that acoustic information, typically in the form of narration, overlaps with action sequences, thereby providing infants with a bottom-up guide to attend to relevant parts and to find structure within them. The authors developed a computational model of the multimodal interplay of action and language in tutoring situations. This chapter presents the results of applying this model to multimodal parent-infant interaction data. Results are twofold and indicate that (a) infant-directed interaction is more structured than adult-directed interaction in that it contains more packages, and these packages have fewer motion segments; and (b) the synchronous structure within infant-directed packages contains redundant information making it possible to solve the reference problem when tying color adjectives to a moving object.

Educating attention: recruiting, maintaining, and framing eye contact in early natural mother-infant interactions - Nomikou, Iris; Rohlfing, Katharina; Szufnarowska, Joanna (Interaction Studies)
In a longitudinal naturalistic study, we observed German mothers interacting with their infants when they were 3 and 6 months old. Pursuing the idea that infants’ attention is socialized in everyday interactions, we explored whether eye contact is reinforced selectively by behavioral modification in the input provided to infants. Applying a microanalytical approach focusing on the sequential organization of interaction, we explored how the mother draws the infant’s attention to herself and how she tries to maintain attention when the infant is looking at her. Results showed that eye contact is reinforced by specific infant-directed practices: interrogatives and conversational openings, multimodal stimulation, repetition, and imitation. In addition, these practices are contingent on the infant’s own behavior. By comparing the two data points (3 and 6 months), we showed how the education of attention evolves hand-in-hand with the developing capacities of the infant.
Keywords: interactional adaptation; multimodal input; social learning; ecology of attention; eye contact

A story about a word: does narrative presentation promote learning of a spatial preposition in German two-year-olds? - Nachtigäller, Kerstin; Rohlfing, Katharina; McGregor, Karla K. (Journal of Child Language)
We trained forty German-speaking children aged 1;8–2;0 in their comprehension of UNTER [UNDER]. The target word was presented within semantically organized input in the form of a ‘narrative’ to the experimental group and within ‘unconnected speech’ to the control group. We tested children’s learning by asking them to perform an UNDER-relation before, immediately after, and again one day after the training using familiarized and unfamiliarized materials. Compared to controls, the experimental group learned better and retained more. Children with advanced expressive lexicons in particular were aided in generalizing to unfamiliarized materials by the narrative presentation. This study extends our understanding of how narrations scaﬀold young children’s enrichment of nascent word knowledge.

Das Leuphana College: Ein in Europa einzigartiges Hochschulmodell – Innovative hochschuldidaktische Veranstaltungsformate. - Seifert, Andreas; Schütz, Julia; Gunkel, Marjaana; Beck, Karin; Balsam, Rebecca; Newig, Jens; Hellmann, Karina; Teigeler, Mareike (DGHD-Tagung „Professionalisierung der Hochschuldidaktik”)

Microdynamics of Interaction: Capturing and Modeling Infants' Social Learning - Rohlfing, Katharina; Deak, Gedeon O. (IEEE Transactions on Autonomous Mental Development)

Frühkindliche Semantik. Eine Einführung - Rohlfing, Katharina

Which Semantic Synchrony? - Rohlfing, Katharina; Grimminger, Angela; Nachtigäller, Kerstin

Qualitätssicherung im bildungswissenschaftlichen Studium – methodologische Überlegungen. - Seifert, Andreas (AEPF-Tagung „Empirische Bildungsforschung und evidenzbasierte Reformen im Bildungswesen”)

Erwerben Lehramtsstudierende pädagogisches Professionswissen? - Seifert, Andreas (Spring School der Forschungsgruppe Schul- und Unterrichtsentwicklung „Professio-nalisierung von Lehrkräften”)

Young children's dialogical actions: The beginnings of purposeful intersubjectivity - Rączaszek-Leonardi, Joanna; Nomikou, Iris; Rohlfing, Katharina (IEEE Transactions on Autonomous Mental Development)

Asymmetry and adaptation in social interaction: A micro-analytic perspective - Rohlfing, Katharina; Nomikou, Iris; Pitsch, Karola (Interaction Studies)

Das Vorlesen von Kinderbüchern als implizites Mittel zur Sprachförderung im Bereich Grammatik - Lehmden von, Friederike; Kauffeldt, Johanna; Belke, Eva; Rohlfing, Katharina (Praxis Sprache)

Learning new words in unfamiliar frames from direct and indirect teaching. - Rohlfing, Katharina; Salas Poblete, Juana; Frank, Joublin

The Development of Purposeful Intersubjectivity - Rączaszek-Leonardi, Joanna; Nomikou, Iris; Rohlfing, Katharina

Effekte eines wortschatzbasierten Lesestrategietrainings auf überfachliche Kompetenzen bei Schülerinnen und Schülern im Grundschulalter. Vortrag auf der Tagung der DGfE-Sektion Empirische Bildungsforschung. AEPF/KBBB 2013 - Förster, Sabrina; Hellmich, Frank

Effektivität eines wortschatzbasierten Lesestrategietrainings bei Kindern mit Deutsch als Zweitsprache in der Grundschule. Vortrag auf der 1.Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Hellmich, Frank; Förster, Sabrina

Individuelle Rückmeldungen und Kompetenzerwerb im Leseunterricht der Grundschule. Vortrag auf der Tagung der DGfE-Sektion Empirische Bildungsforschung. AEPF/KBBB 2013 - Hellmich, Frank; Hoya, Fabian Karl

Schulpädagogik des Primarbereichs – Aktuelle Herausforderungen in Forschung, Lehre und Unterrichtspraxis - Hellmich, Frank

Rückmeldungen und Lehr-Lernprozesse im Grundschulunterricht - Hellmich, Frank

Entwicklung selbstbezogener Kognitionen und Motivationen von Grundschulkindern mit Deutsch als Zweitsprache nach der Implementation eines wortschatzbasierten Lesestrategietrainings. Vortrag auf der Tagung „Gemeinsam anders lehren und lernen – Wege in die inklusive Bildung“. Gemeinsame Jahrestagung der DGfE Kommission Grundschulforschung und Didaktik der Primarstufe und der DGfE Sektion Sonderpädagogik - Förster, Sabrina; Hellmich, Frank

Einstellungen von Lehrkräften zum inklusiven Unterricht in der Grundschule. Vortrag im Rahmen des Symposiums „Qualität inklusiven Unterrichts in der Grundschule“ auf der Tagung „Gemeinsam anders lehren und lernen – Wege in die inklusive Bildung“. Gemeinsame Jahrestagung der DGfE Kommission Grundschulforschung und Didaktik der Primarstufe und der DGfE Sektion Sonderpädagogik - Görel, Gamze; Ort, Margarita; Hellmich, Frank

Individuelles Feedback in heterogen zusammengesetzten Lerngruppen im Leseunterricht der Grundschule – Befunde aus einer empirischen Studie. Vortrag auf der Tagung „Gemeinsam anders lehren und lernen – Wege in die inklusive Bildung“. Gemeinsame Jahrestagung der DGfE Kommission Grundschulforschung und Didaktik der Primarstufe und der DGfE Sektion Sonderpädagogik - Hoya, Fabian Karl; Hellmich, Frank

Möglichkeiten der Lesestrategieförderung bei leistungsschwächeren Kindern im Leseunterricht der Grundschule. Vortrag auf der Tagung der Deutschen Gesellschaft für Lesen und Schreiben (DGLS) - Förster, Sabrina; Hellmich, Frank

Tagungsbericht: 126. Jahresversammlung des Vereins für niederdeutsche Sprachforschung in Flensburg. - Wallmeier, Nadine; Menke, Kirsten (Korrespondenzblatt des Vereins für niederdeutsche Sprachforschung)

Coherent control of interaction and entanglement of a Rydberg atom with few photons - Sharapova, Polina; Tikhonova, O V (Laser Physics Letters)
Keywords: Physics and Astronomy (miscellaneous); Instrumentation

Martin representation and Relative Fatou Theorem for fractional Laplacian with a gradient perturbation - Graczyk, Piotr; Jakubowski, Tomasz; Luks, Tomasz (Positivity)

Gemeinwesenarbeit und die Aktivierung von sozialem Kapital - Landhäußer, Sandra (Handbuch Gemeinwesenarbeit)
Wie ist der derzeitige Wissensstand in der Gemeinwesenarbeit? Das Handbuch systematisiert und aktualisiert das Theorie- und Praxiswissen für dieses Gebiet. Vorgestellt werden Traditionen und Diskussionen insbesondere in Deutschland, Österreich und der Schweiz. In der Praxis stellt sich Gemeinwesenarbeit einerseits als Arbeitsprinzip und als Fachkonzept dar, das an Aktualität gewonnen hat, andererseits aber zwischen Sozialraumorientierung und aktivierendem Sozialstaat zu verschwimmen droht. Die AutorInnen arbeiten daher das Konzept Gemeinwesenarbeit historisch auf und überprüfen es daraufhin, welche Beiträge es für eine fachtheoretische Weiterentwicklung der Sozialen Arbeit aktuell einbringen kann. Es werden die verschiedenen Handlungsfelder der Gemeinwesenarbeit betrachtet, nicht mit dem Ziel einer „Leistungsschau“, sondern vielmehr als kritische Würdigung.
Keywords: Gemeinwesenarbeit; Sozialraum; Zivilgesellschaft

Forschendes Lernen in Lernwerkstätten - Kottmann, Brigitte (Studieren in Lernwerkstätten – Potentiale und Herausforderungen für die Lehrerbildung)
Das Forschende Lernen gehörte von Beginn an zu den expliziten Grundprinzipien von Lernwerkstattsarbeit. So formulierte Karin Ernst bereits 1993: „… dass Erwachsene selbst anders lernen müssen – aktiv, forschend, entdeckend, kreativ, offen –, um mit Kindern auf andere Weise Schule machen zu können“ (Ernst 1993, 18).

Locally Most Powerful Invariant Tests for Correlation and Sphericity of Gaussian Vectors - Ramírez, D.; Vía, J.; Santamaría, I.; Scharf, L. L. (IEEE Trans.\ Inform.\ Theory)
In this paper we study the existence of locally most powerful invariant tests (LMPIT) for the problem of testing the covariance structure of a set of Gaussian random vectors. The LMPIT is the optimal test for the case of close hypotheses, among those satisfying the invariances of the problem, and in practical scenarios can provide better performance than the typically used generalized likelihood ratio test (GLRT). The derivation of the LMPIT usually requires one to find the maximal invariant statistic for the detection problem and then derive its distribution under both hypotheses, which in general is a rather involved procedure. As an alternative, Wijsman’s theorem provides the ratio of the maximal invariant densities without even finding an explicit expression for the maximal invariant. We first consider the problem of testing whether a set of N-dimensional Gaussian random vectors are uncorrelated or not, and show that the LMPIT is given by the Frobenius norm of the sample coherence matrix. Second, we study the case in which the vectors under the null hypothesis are uncorrelated and identically distributed, that is, the sphericity test for Gaussian vectors, for which we show that the LMPIT is given by the Frobenius norm of a normalized version of the sample covariance matrix. Finally, some numerical examples illustrate the performance of the proposed tests, which provide better results than their GLRT counterparts.

Amplify-and-Forward Strategies in the Two-Way Relay Channel with Analog Tx-Rx Beamforming - Lameiro, Christian; Vía, Javier; Santamaría, Ignacio (IEEE Trans. Veh. Techn.)
In this paper, we study the multiple-input multiple-output two-way relay channel (MIMO-TWRC) when the nodes and relay use analog beamforming. Following the amplify-andforward (AF) strategy, the problem consists of finding the transmit and receive beamformers of the nodes and relay (as well as the power allocated to each one) that achieve the boundary of the optimal rate region. To solve it, we first express the optimal node beamformers in terms of relay beamformers and then show that the optimal rate region can efficiently be characterized using convex optimization techniques. We also extend our study to the multiple-relay scenario when the source nodes are single antenna and propose a distributed algorithm to compute the relay beamforming matrices. The proposed algorithm consists of solving two different subproblems. First, each individual TWRC is optimized independently. Next, a distributed beamforming is applied to make the signals from the relays add up coherently at the source nodes. Numerical examples are provided to illustrate the performance of the proposed techniques and to compare the performance of analog beamforming architectures against conventional MIMO schemes that operate at the baseband.

Computing the Degrees of Freedom for Arbitrary MIMO Interference Channels - Lameiro, Christian; Vía, Javier; Beltrán, Carlos; Santamaría, Ignacio (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
In this paper we provide an efficient procedure to compute the total number of degrees of freedom (DoF), achievable by linear beamforming, of the $K$-user multiple-input multiple-output (MIMO) interference channel with an arbitrary number of Tx-Rx antennas at each link. Firstly, we derive an analytical outer bound that generalizes the results that exist for the symmetric $K$-user $M\timesN$ interference channel. Secondly, we obtain a tighter bound by solving a convex optimization problem that includes as constraints the DoF characterizations for point-to-point MIMO links and for 2-user interference channels. The solution to this convex problem admits an interesting waterfilling interpretation. Finally, exploiting this outer bound and using a recently proposed feasibility test, we show that it is possible to obtain the DoF for any interference channel in an efficient way. Some simulations results are included to illustrate the tightness of the derived bounds, as well as to study the DoF achievable for the 4-user channel when we distribute the total number of antennas among users and between transmitters and receivers in different ways.

Robust stability of networks of iISS systems: Construction of sum-type Lyapunov functions - Ito, Hiroshi; Jiang, Zhong-Ping; Dashkovskiy, Sergey; Rüffer, Björn S. (IEEE Trans. Autom. Control)
This paper gives a solution to the problem of verifying stability of networks consisting of integral input-to-state stable (iISS) subsystems. The iISS small-gain theorem developed recently has been restricted to interconnections of two subsystems. For large-scale systems, stability criteria relying only on gain-type information that were previously developed address only input-to-state stable (ISS) subsystems. To address the stability problem involving iISS subsystems interconnected in general structure, this paper shows how to construct Lyapunov functions of the network by means of a sum of nonlinearly rescaled individual Lyapunov functions of subsystems under an appropriate small-gain condition.

Power-CCA: Maximizing the Correlation Coefficient between the Power of Projections - Ramírez, D.; Schreier, P. J.; Vía, J.; Nikulin, V. V. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
This work presents a variation of canonical correlation analysis (CCA), where the correlation coefficient between the instantaneous power of the projections is maximized, rather than between the projections themselves. The resulting optimization problem is not convex, and we have to resort to a sub-optimal approach. Concretely, we propose a two-step solution consisting of the singular value decomposition (SVD) of a "coherence" matrix followed by a rank-one matrix approximation. This technique is applied to blindly recovering signals in a model that is motivated by the study of neuronal dynamics in humans using electroencephalography (EEG) and magnetoencephalography (MEG). A distinctive feature of this model is that it allows recovery of amplitude-amplitude coupling between neuronal processes.

Quantization-loss analysis for array signal-source localization - Stein, Manuel; Mezghani, Amine; Nossek, Josef A. (Proc.\ ITG Int.\ Work. Smart Ant.)

Quantization-loss reduction for 1-bit BOC positioning - Wendler, Friederike; Stein, Manuel; Mezghani, Amine; Nossek, Josef A. (ION Int.\ Tech. Meet.)

A unified framework for regularized linear estimation in communication systems - Tong, Jun; Schreier, Peter J. (Signal Process.)
Two concerns often arise simultaneously when applying linear estimation in communication systems: the computational complexity can be prohibitively high when the system size is large, and the performance may degrade dramatically when the presumed model is mismatched with the actual system. In this paper, we introduce a subspace expansion framework to jointly address these concerns, in which the observation is first projected onto a lower-dimensional subspace and then the solution of the projected problem is regularized. We discuss two projection methods based on eigensubspace and Krylov subspace expansions. We show that the Krylov subspace projection provides an economical solution to regularized linear estimation. We also compare different regularization methods, such as principal components and diagonal loading. We show that diagonal loading generally outperforms other alternatives and that Krylov subspace rank reduction can yield a regularization effect close to diagonal loading. Finally, we investigate the impact of preconditioning on the performance and complexity for mismatched modeling and propose a loaded preconditioner, which can reduce complexity as well as preserve the regularization effect. Under the proposed framework, various regularization schemes are studied and some guidelines for choosing the right scheme are provided.

A Two-Phase Approach to Stability of Networks Given in iISS Framework: Utilization of a Matrix-Like Criterion - Ito, Hiroshi; Rüffer, Björn S. (Proc. IEEE American Contr. Conf.)
This article is concerned with global asymptotic stability (GAS) of dynamical networks. The case when subsystems are integral input-to-state stable (iISS) has been recognized as notoriously difficult to deal with in the literature. In fact, the lack of energy dissipation for large input denies direct application of the small-gain argument for input-to-state stable (ISS) subsystems. Here for networks consisting of iISS subsystems it is demonstrated that a two-phase approach allows us to make use of the ISS small-gain argument by separating a trajectory into a transient and a subsequent convergence. In contrast to the previous iISS results, the two-phase approach immediately leads to a sufficient criterion for GAS of general nonlinear networks in a matrix-like form (order condition).

Convergent Systems vs. Incremental Stability - Rüffer, Björn S.; van de Wouw, Nathan; Mueller, Markus (Systems Control Lett.)
Two similar stability notions are considered; one is the long established notion of convergent systems, the other is the younger notion of incremental stability. Both notions require that any two solutions of a system converge to each other. Yet these stability concepts are different, in the sense that none implies the other, as is shown in this paper using two examples. It is shown under what additional assumptions one property indeed implies the other. Furthermore, this paper contains necessary and sufficient characterizations of both properties in terms of Lyapunov functions.

A Razumikhin approach for the incremental stability of delayed nonlinear systems - Chaillet, Antoine; Yu. Pogromsky, Alexander; Rüffer, Björn S. (Proc. 52nd IEEE Conf. Decis. Control)
This paper provides sufficient conditions for the incremental stability of time-delayed nonlinear systems. It relies on the Razumikhin-Lyapunov approach, which consists in invoking small-gain arguments by treating the delayed state as a feedback perturbation. The results are valid for multiple delays, as well as bounded time-varying delays. We provide conditions under which the limit solution of a time-delayed nonlinear system to a periodic (resp. constant) input is itself periodic and of the same period (resp. constant). As an illustration, a specific focus is given on a class of delayed Lur’e systems.

Optical coherence tomography assessment of vessel wall degradation in thoracic aortic aneurysms - Real, Eusebio; Eguizabal, Alma; Pontón, Alejandro; Díez, Marta Calvo; Val-Bernal, José Fernando; Mayorga, Marta; Revuelta, José M.; López-Higuera, José M.; Conde, Olga M. (J. Biomed. Opt.)

Separable Lyapunov functions for monotone systems - Rantzer, Anders; Rüffer, Björn S.; Dirr, Gunther (Proc. 52nd IEEE Conf. Decis. Control)
Separable Lyapunov functions play vital roles, for example, in stability analysis of large-scale systems. A Lyapunov function is called max-separable if it can be decomposed into a maximum of functions with one-dimensional arguments. Similarly, it is called sum-separable if it is a sum of such functions. In this paper it is shown that for a monotone system on a compact state space, asymptotic stability implies existence of a max-separable Lyapunov function. We also construct two systems on a non-compact state space, for which a max-separable Lyapunov function does not exist. One of them has a sum-separable Lyapunov function. The other does not.

Regularized Preconditioning for Krylov Subspace Equalization of OFDM Systems over Doubly Selective Channels - Tong, Jun; Schreier, Peter J. (IEEE Wireless Comm. Lett.)

Joint space-time interference mitigation for embedded multi-antenna GNSS receivers - Castañeda, Mario; Stein, Manuel; Antreich, Felix; Tasdemir, Emrah; Kurz, Lothar; Noll, Tobias G.; Nossek, Josef A. (ION GNSS+)

Direct identification of breast cancer pathologies using blind separation of label-free localized reflectance measurements - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose M.; Conde, Olga M. (Biomed. Opt. Express)
Breast tumors are blindly identified using Principal (PCA) and Independent Component Analysis (ICA) of localized reflectance measurements. No assumption of a particular theoretical model for the reflectance needs to be made, while the resulting features are proven to have discriminative power of breast pathologies. Normal, benign and malignant breast tissue types in lumpectomy specimens were imaged ex vivo and a surgeon-guided calibration of the system is proposed to overcome the limitations of the blind analysis. A simple, fast and linear classifier has been proposed where no training information is required for the diagnosis. A set of 29 breast tissue specimens have been diagnosed with a sensitivity of 96% and specificity of 95% when discriminating benign from malignant pathologies. The proposed hybrid combination PCA-ICA enhanced diagnostic discrimination, providing tumor probability maps, and intermediate PCA parameters reflected tissue optical properties.

Time-to-space conversion of ultrafast waveforms at 155 μm in a planar periodically poled lithium niobate waveguide - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Post-selection free, integrated optical source of non-degenerate, polarization entangled photon pairs - Herrmann, Harald; Yang, Xu; Thomas, Abu; Poppe, Andreas; Sohler, Wolfgang; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef U.; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Silberhorn, Christine; Leuchs, Gerd; Marquardt, Christoph (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Increasing the Dimensionality of Quantum Walks Using Multiple Walkers - Rohde, Peter P.; Schreiber, Andreas; Štefaňák, Martin; Jex, Igor; Gilchrist, Alexei; Silberhorn, Christine (Journal of Computational and Theoretical Nanoscience)
Keywords: Electrical and Electronic Engineering; Computational Mathematics; Condensed Matter Physics; General Materials Science; General Chemistry

Spatio-spectral characteristics of parametric down-conversion in waveguide arrays - Kruse, R; Katzschmann, F; Christ, A; Schreiber, A; Wilhelm, S; Laiho, K; Gábris, A; Hamilton, C S; Jex, I; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Technik - Alpsancar, Suzana (Die Entwicklung der Psyche in der Geschichte der Menschheit. Auf dem Weg zu einem integrativen Ansatz)

Sooner or Later? – Paradoxical Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren (European Accounting Review)

Advance Pricing Agreements (APAs) als Instrument zur Vermeidung von Verrechnungspreiskonflikten – eine kritische Betrachtung - Vollert, Pia; Eikel, Carolin; Sureth-Sloane, Caren (Steuer und Wirtschaft)

A New Model of Higher Education in the European Context - The Leuphana Experience. - Gunkel, Marjaana; Schütz, Julia; Seifert, Andreas; Scharlau, Ingrid; Beck, Karin; Heuer, Claudia (INTED2013 Conference Proceedings: 7th International Technology, Education and Development Conference March 4th-6th, 2013 – Valencia, Spain)

Inszenierungen eines Affekts. Scham und ihre Konstruktion in der Literatur der Moderne. - Heidgen, Michael

To err is human (-like): Effects of robot gesture on perceived anthropomorphism and likeability - Salem, Maha; Eyssel, Friederike Anne; Rohlfing, Katharina; Kopp, Stefan; Joublin, Frank (International Journal of Social Robotics)

Dokumentation der Studie ProLEG: Professionalisierung von Lehrkräften für einen reflektierten Umgang mit Ethnizität und Geschlecht in der Grundschule. Kurz-Dokumentation ausgewählter Daten und Ergebnisse (PLAZ-Forum (Lehrerausbildung und Schule in der Diskussion))

Potential und Herausforderung von Kompetenzforschung auf der Grundlage von IRT-Modellen. - Seifert, Andreas (Kompetenzmessung und -modellierung in den Fachdidaktiken)

Der Hof. Ein Ort kulturellen Handelns von Frauen in der Frühen Neuzeit

Von Opernszenen zum Sprech-Theater: Die Gretchentragödie in Schauspielmusiken zu „Faust“ im 19. Jahrhundert - Tumat, Antje (Vorausdeutungen und Rückblicke. Goethe und Goethe-Rezeption zwischen Klassik und Moderne)

Language lateralization represented by spatiotemporal mapping of magnetoencephalography. - Tanaka, N; Liu, H; Reinsberger, Claus; Madsen, JR; Bourgeois, BF; Dworetzky, BA; Hämäläinen, MS; Stufflebeam, SM (AJNR Am J Neuroradiol)

A millimeter wave quad-phase ring oscillator using 0.13 µm SiGe BiCMOS HBT technology - Ali, U.; Thiede, Andreas (2013 International Semiconductor Conference Dresden - Grenoble (ISCDG))

Zeolitic imidazolate framework-71 nanocrystals and a novel SOD-type polymorph: solution mediated phase transformations, phase selection via coordination modulation and a density functional theory derived energy landscape - Schweinefuß, Maria E.; Springer, Sergej; Baburin, Igor A.; Hikov, Todor; Huber, Klaus; Leoni, Stefano; Wiebcke, Michael (Dalton Transactions)
Keywords: Inorganic Chemistry

Kinetic and Structural Features of a Dyestuff Coaggregation Studied by Time-Resolved Static Light Scattering - Michels, Rolf; Hertle, Yvonne; Hellweg, Thomas; Huber, Klaus (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Co-Aggregation of Two Anionic Azo Dyestuffs at a Well-Defined Stoichiometry - Michels, Rolf; Sinemus, Thomas; Hoffmann, Jan; Brutschy, Bernhard; Huber, Klaus (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Morphology of Blends with Cross-Linked PMMA Microgels and Linear PMMA Chains - Schneider, M.; Michels, R.; Pipich, V.; Goerigk, G.; Sauer, V.; Heim, H.-P.; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

SAXS and ASAXS on Dilute Sodium Polyacrylate Chains Decorated with Lead Ions - Lages, Sebastian; Goerigk, Günter; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Einsatzmöglichkeiten und Anwendungsgrenzen der digitalen Bildkorrelation zur Frühdetektion struktureller und funktioneller Schädigungen und Versagensvorhersage in metallischen Werkstoffen, Werkstoffverbunden und Verbundwerkstoffen - Gorny, Bernhard

Running performance analysis in basketball using recorded trajectory data - Jakobsmeyer, Rasmus; Schnittker, Reinhard; Zorn, Rene; Rückert, Ulrich; Baumeister, Jochen (Performance Analysis of Sport IX)

Triggered Indistinguishable Single Photons with Narrow Line Widths from Site-Controlled Quantum Dots - Jöns, Klaus D.; Atkinson, P.; Müller, M.; Heldmaier, M.; Ulrich, S. M.; Schmidt, O. G.; Michler, P.

Qualitätsmanagement in der zivilen Gefahrenabwehr : Optimierung von Führungsprozessen durch interaktive SOPs - Becker, Tobias

Phenomenological Process Simulation and Multiscale Tool Simulation Directed to a Hybrid Forming Process - Sauerland, Kim-Henning

Ursula Kramer: Schauspielmusik am Hoftheater in Darmstadt 1810–1918. Spiel-Arten einer selbstverständlichen Theaterpraxis (= Beiträge zur mittelrheinischen Musikgeschichte 41) - Tumat, Antje (Die Musikforschung)

Ein Fahrerassistenzsystem zur prädiktiven Planung energie- und zeitoptimaler Geschwindigkeitsprofile mittels Mehrzieloptimierung - Gausemeier, Sandra Fabia

Qualifizierung der Direktverschraubung in Fließlochdurchzüge für Aluminiumleichtbaustrukturen des Automobils - Burs, Christian

Approximation, Proof Systems, and Correlations in a Quantum World - Gharibian, Sevag
This thesis studies three topics in quantum computation and information: The approximability of quantum problems, quantum proof systems, and non-classical correlations in quantum systems. In the first area, we demonstrate a polynomial-time (classical) approximation algorithm for dense instances of the canonical QMA-complete quantum constraint satisfaction problem, the local Hamiltonian problem. In the opposite direction, we next introduce a quantum generalization of the polynomial-time hierarchy, and define problems which we prove are not only complete for the second level of this hierarchy, but are in fact hard to approximate. In the second area, we study variants of the interesting and stubbornly open question of whether a quantum proof system with multiple unentangled quantum provers is equal in expressive power to a proof system with a single quantum prover. Our results concern classes such as BellQMA(poly), and include a novel proof of perfect parallel repetition for SepQMA(m) based on cone programming duality. In the third area, we study non-classical quantum correlations beyond entanglement, often dubbed "non-classicality". Among our results are two novel schemes for quantifying non-classicality: The first proposes the new paradigm of exploiting local unitary operations to study non-classical correlations, and the second introduces a protocol through which non-classical correlations in a starting system can be "activated" into distillable entanglement with an ancilla system. An introduction to all required linear algebra and quantum mechanics is included.

QMA variants with polynomially many provers - Gharibian, Sevag; Sikora, Jamie; Upadhyay, Sarvagya (Quantum Information & Computation)
We study three variants of multi-prover quantum Merlin-Arthur proof systems. We first show that the class of problems that can be efficiently verified using polynomially many quantum proofs, each of logarithmic-size, is exactly MQA (also known as QCMA), the class of problems which can be efficiently verified via a classical proof and a quantum verifier. We then study the class BellQMA(poly), characterized by a verifier who first applies unentangled, nonadaptive measurements to each of the polynomially many proofs, followed by an arbitrary but efficient quantum verification circuit on the resulting measurement outcomes. We show that if the number of outcomes per nonadaptive measurement is a polynomially-bounded function, then the expressive power of the proof system is exactly QMA. Finally, we study a class equivalent to QMA(m), denoted SepQMA(m), where the verifier's measurement operator corresponding to outcome "accept" is a fully separable operator across the m quantum proofs. Using cone programming duality, we give an alternate proof of a result of Harrow and Montanaro [FOCS, pp. 633--642 (2010)] that shows a perfect parallel repetition theorem for SepQMA(m) for any m.

In-situ Strukturcharakterisierung von CNT in polymerbasierten Nanokompositen Methodenentwicklung und Anwendung - Gerkens, Stefan

Privacy and Security in Europe. The Privacy & Security-Research Paper Series, edited by Emilio Mordini and Christian Fuchs. Research Paper Number 6 - Fuchs, Christian

Grundlegende Untersuchung der Prozess- und Werkzeugparameter und ihrer Wechselwirkungen für das thermo-mechanisch unterstützte inkrementelle Umformverfahren des Reib-Drückens - Hornjak, Daniel

Theorising and Analysing Digital Labour: From Global Value Chains to Modes of Production - Fuchs, Christian (The Political Economy of Communication)

Political Economy and Surveillance Theory - Fuchs, Christian (Critical Sociology)

The Diamond Model of Open Access Publishing: Why Policy Makers, Scholars, Universities, Libraries, Labour Unions and the Publishing World Need to Take Non-Commercial, Non-Profit Open Access Serious - Fuchs, Christian; Sandoval, Marisol (tripleC: Communication, Capitalism & Critique)

What Is Digital Labour? What Is Digital Work? What’s Their Difference? And Why Do These Questions Matter for Understanding Social Media? - Fuchs, Christian; Sevignani, Sebastian (tripleC)

Capitalism or Information Society? The Fundamental Question of the Present Structure of Society - Fuchs, Christian (European Journal of Social Theory)

Societal and Ideological Impacts of Deep Packet Inspection (DPI) Internet Surveillance - Fuchs, Christian (Information, Communication and Society)

Class and Exploitation on the Internet - Fuchs, Christian (Digital Labor. The Internet as Playground and Factory)

„Reißverschluß in 600m“ – Über textile Wahrnehmungsmuster - Kraft, Kerstin

Sprachspiele der Ethik - Matzner, Tobias (Perspektiven philosophischer Forschung II)

Vita variabilis: Handelnde und ihre Welt nach Hannah Arendt und Ludwig Wittgenstein - Matzner, Tobias

Self-organization of nanospheres in trenches on silicon surfaces - Brassat, Katharina; Assion, Fabian; Hilleringmann, Ulrich; Lindner, Jörg K. N. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Titanium Disilicide as High-Temperature Contact Material for Thermoelectric Generators - Assion, F.; Schönhoff, M.; Hilleringmann, Ulrich (Journal of Electronic Materials)
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Enhanced organic light-emitting diode based on a columnar liquid crystal by integration in a microresonator - Kasdorf, Olga; Vollbrecht, Joachim; Ohms, Benjamin; Hilleringmann, Ulrich; Bock, Harald; Kitzerow, Heinz-S. (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Femtosecond quantum interference control of electrical currents in GaAs: Signatures beyond the perturbative χ(3) limit - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Duc, H. T.; Meier, Torsten; Betz, M. (Physical Review B)

Zwischen Santini-Sammlung und Choralreform: Zur Biographie des Domvikars und Domchordirektors Bernhard Quante - Höink, Dominik („Sacrae Musices Cultor et Propagator“: Internationale Tagung zum 150. Todesjahr des Musiksammlers, Komponisten und Bearbeiters Fortunato Santini.)

„Declaration of Independence in Art“. Nationales Denken und das US-amerikanische Oratorium im 19. Jahrhundert - Höink, Dominik (Grenzüberschreitende Religion. Vergleichs- und Kulturtransferstudien zur neuzeitlichen Geschichte)

„Patriarch ächt deutscher Kirchenmusik“. Aspekte konfessioneller Händel-Bilder im 19. Jahrhundert - Höink, Dominik (Händel-Jahrbuch)

Newton's cradles in optics: From N-soliton fission to soliton chains - Driben, R.; Malomed, B.A.; Yulin, A. V.; Skryabin, D.V. (Physical Review A)
A mechanism for creating a Newton's cradle (NC) in nonlinear light wave trains under the action of the third-order dispersion (TOD) is demonstrated. The formation of the NC structure plays an important role in the process of fission of higher-order (N) solitons in optical fibers. After the splitting of the initial N soliton into a nonuniform chain of fundamental quasisolitons, the tallest one travels along the entire chain, through consecutive collisions with other solitons, and then escapes, while the remaining chain of pulses stays as a bound state, due to the radiation-mediated interaction between them. Increasing the initial soliton's order, N, leads to the transmission through, and release of additional solitons with enhanced power, along with the emission of radiation, which may demonstrate a broadband supercontinuum spectrum. The NC dynamical regime remains robust in the presence of extra perturbations, such as the Raman and self-steepening effects, and dispersion terms above the third order. It is demonstrated that essentially the same NC mechanism is induced by the TOD in finite segments of periodic wave trains (in particular, soliton chains). A difference from the mechanical NC is that the TOD-driven pulse passing through the soliton array collects energy and momentum from other solitons. Thus, uniform and nonuniform arrays of nonlinear wave pulses offer an essential extension of the mechanical NC, in which the quasiparticles, unlike mechanical beads, interact inelastically, exchanging energy and generating radiation. Nevertheless, the characteristic phenomenology of NC chains may be clearly identified in these nonlinear-wave settings too.

Instabilities, solitons and rogue waves in PT-coupled nonlinear waveguides - Bludov, Y.V.; Driben, R.; Konotop, V.V.; Malomed, B.A. (Journal of Optics)
We considered the modulational instability of continuous-wave backgrounds, and the related generation and evolution of deterministic rogue waves in the recently introduced parity–time (P T)-symmetric system of linearly coupled nonlinear Schrödinger equations, which describes a Kerr-nonlinear optical coupler with mutually balanced gain and loss in its cores. Besides the linear coupling, the overlapping cores are coupled through the cross-phase-modulation term too. While the rogue waves, built according to the pattern of the Peregrine soliton, are (quite naturally) unstable, we demonstrate that the focusing cross-phase-modulation interaction results in their partial stabilization. For P T-symmetric and antisymmetric bright solitons, the stability region is found too, in an exact analytical form, and verified by means of direct simulations